Ovarian hormones modulate multidrug resistance transporters in the ovary - Lynae M Brayboy; Laura O Knapik; Sokunvichet Long; Mollie Westrick; Gary M Wessel (BMC, 2018)
Abstract Background Multidrug resistance transporters (MDRs) are transmembrane proteins that efflux metabolites and xenobiotics. They are highly conserved in sequence and function in bacteria and eukaryotes and play important roles in cellular homeostasis, as well as in avoidance of antibiotics and cancer therapies. Recent evidence also documents a critical role in reproductive health and in protecting the ovary from environmental toxicant effects. The most well understood MDRs are MDR-1 (P-glycoprotein (P-gp) also known as ABCB1) and BCRP (breast cancer resistance protein) and are both expressed in the ovary. We have previously shown that MDR-1 mRNA steady state expression changes throughout the murine estrous cycle, but expression appears to increase in association with the surge in estradiol during proestrus. Methods Here we test the model that MDR-1 and BCRP are regulated by estrogen, the major hormonal product of the ovary. This was performed by administering 6-week-old female mice either sesame oil (vehicle control) or oral ethinyl estradiol at 1 μg, 10 μg, and 100 μg or PROGESTERONE at 0.25mg, 0.5 mg or 1 mg or a combination of both for 5 days. The mice were then sacrificed, and the ovaries were removed and cleaned. Ovaries were used for qPCR, immunoblotting, and immnunolabeling. Results We found that oral ethinyl estradiol did not influence the steady state mRNA of MDR-1 or BCRP. Remarkably, the effect on mRNA levels neither increased or decreased in abundance upon estrogen exposures. Conversely, we observed less MDR-1 protein expression in the groups treated with 1 μg and 10 μg, but not 100 μg of ethinyl estradiol compared to controls. MDR-1 and BCRP are both expressed in pre-ovulatory follicles. When we tested progesterone, we found that MDR-1 mRNA increased at the dosages of 0.25 mg and 0.5 mg, but protein expression levels were not statistically significant. Combined oral ethinyl estradiol and progesterone significantly lowered both MDR-1 mRNA and protein. Conclusions Progesterone appears to influence MDR-1 transcript levels, or steady state levels. This could have implications for better understanding how MDR-1 can be modulated during times of toxic exposure. Understanding the normal physiology of MDR-1 in the ovary will expand the current knowledge in cancer biology and reproduction.